ANALISIS PENGARUH EKSPOR, IMPOR, NILAI TUKAR, DAN SUKU BUNGA TERHADAP CADANGAN DEVISA DI INDONESIA - Aceh, Astuti Yeni; Rahim, Manat; Ilyas, Ilyas (Universitas Halu Oleo, 2023)
This study aims to analyze the effect of exports, imports, exchange rates, and interest rates on foreign exchange reserves in Indonesia. Both partially and simultaneously. The data used is time series data from 2009 to 2021. The data is processed with eviews 10 using the Error Correction Model (ECM). The results showed that in the short term, the export variable has a positive and significant effect on foreign exchange reserves in Indonesia, imports and exchange rates have a positive and insignificant effect on foreign exchange reserves in Indonesia, while interest rates have a negative and significant effect on foreign exchange reserves in Indonesia. In the long term, the export variable has a positive and significant effect on foreign exchange reserves in Indonesia, the import variable has a positive and insignificant effect on foreign exchange reserves in Indonesia, the exchange rate has a positive and significant effect on foreign exchange reserves in Indonesia, while interest rates have a negative and significant effect on foreign exchange reserves in Indonesia. Indonesia.